Classification of Developmental Language Disorders (DLD) - An Exploratory Study - Geetha Y. V.; Prema K.S. (Journal of All India Institute of Speech and Hearing, 2007)
Developmental Language Disorders (DLDs) pose a great diagnostic challenge to the practicing speech language pathologists in view of the complexities and variability in their manifestations. This is more so in a country like India where multi-lingual and multi-cultural factors influence the acquisition of speech and language in a child. Most of the children are exposed to a minimum of two languages during their preschool and early school years. The diagnostic process is further complicated by the nonavailability of standardized language assessment tools in the Indian languages. The present study aimed at developing Checklist for the Assessment of Language and Behavior (CALB) that would help in classification of children with DLDs, based on literature and case file information with respect to history of onset and development of language disorder, language comprehension, expression and behaviors associated with DLDs. CALB clearly differentiated 7 groups of children with DLD. Further, the classification of DLDs on the basis of Artificial Neural Network and Discriminant analysis is also discussed.